1988
DOI: 10.21273/hortsci.23.1.196
|View full text |Cite
|
Sign up to set email alerts
|

Translocation and Breakdown of 14C-labeled Paclobutrazol in ‘Nemaguard’ Peach Seedlings

Abstract: ‘Nemaguard’ peach seedlings [Prunus persica (L.) Batsch] were grown in nutrient solution cultures containing 0.36 µM 14C-labeled paclobutrazol (0.59 MBq·liter–1) for 9 days. Microautoradiographs of transverse and longitudinal stem sections showed that 14C activity was localized in the xylem. Tissue extracts showed that the total 14C activity in the plants was distributed predominantly between the roots (40.9%) and leaves (49.1%). The majority of 14C activity in stems and leaves was located in the lowest stem a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…PBZ was also held by roots, translocated through the xylem mainly in the stems, and collected in leaves (Wang et al, 1985). Early and Martin (1988) found that PBZ was metabolized more quickly in apple leaves than in other plant sections.…”
Section: Chemical Structure and Modes Of Applicationmentioning
confidence: 98%
“…PBZ was also held by roots, translocated through the xylem mainly in the stems, and collected in leaves (Wang et al, 1985). Early and Martin (1988) found that PBZ was metabolized more quickly in apple leaves than in other plant sections.…”
Section: Chemical Structure and Modes Of Applicationmentioning
confidence: 98%